Peningkatan Kualitas Konten Visual Melalui Workshop Fotografi Dan Videografi Bagi Mahasiswa Dan Pelaku Konten Digital - Elsa Sapitri; Robhans Vickidella Hartono Putra; Pritta Magfira Zenya; Robby Annand; Wiwin Herwina (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
The development of digital media has increased the demand for engaging, communicative, and high-quality visual content as a means of conveying information, promoting products or services, and building personal brands. However, preliminary observations indicate that students and digital content creators still face various challenges in producing effective visual content, particularly regarding lighting techniques, visual composition, storytelling, and content editing. This community service initiative aims to enhance participants’ knowledge and skills in producing visual content that is more creative, aesthetically pleasing, and aligned with the needs of digital media through photography and videography workshops. The method used was Participatory Action Research (PAR), which actively involved participants in the process of problem identification, action planning, activity implementation, hands-on practice, observation, and reflection. The activities were conducted through presentations, participatory discussions, demonstrations, hands-on practice, and guidance on creating visual content using smartphones. The materials covered included visual branding, visual branding techniques, lighting, composition, shooting angles, storytelling, and content editing. The results of the activities showed an increase in participants’ understanding of the principles of photography and videography, improved skills in producing higher-quality photos and videos, and increased confidence in producing digital content. Additionally, participants were able to apply the visual techniques they learned to create content that is more engaging, communicative, and aligned with the characteristics of social media audiences. Thus, the PAR-based photography and videography workshop has proven effective as an empowerment strategy for improving the quality of visual content and digital literacy among students and digital content creators.